Investigation into overfiring of a modular biomass boiler with an industrial Rankine cycle and supplementary sCO2 Brayton cycle using CFD - Rashid A. Haffejee; Pieter Rousseau; Ryno Laubscher (International Journal of Thermofluids)
In this paper, a grate-fired modular biomass boiler with an existing industrial Rankine cycle and proposed supplementary sCO2 Brayton power generation cycle is analysed at nominal and low load using CFD. The aim is to leverage the higher efficiency of the sCO2 cycle by retrofitting the water-tube boiler with tube-bank sCO2 heat exchangers, and overfiring the furnace to provide the additional heat load. CFD models of the boiler are developed using a Eulerian-Lagrangian approach for two integrated sCO2 heater configurations; a single convective heater configuration, and a dual radiative-convective heater configuration with slight adjustments to the boiler nose geometry. The boiler without any sCO2-integration is also modelled. The CFD models explore the effects of overfiring and geometry adjustments on boiler performance using boundary conditions provided by a 1D thermofluid network model of the integrated cycle.At nominal load, overfiring does not pose any significant problems, indicating feasibility of the sCO2-integrated configurations. At low load, high sCO2 heater tube metal temperatures up to 586°C are observed for the dual configuration, which may impact tube lifetime. The adjustment to the boiler nose for the dual configuration results in higher heat fluxes towards the boiler roof and front wall. Heat uptakes at the convective sCO2 heaters decreased significantly at low load, indicating adjustments may be required to shift the sCO2 cycle operation away from the pseudo-critical point. The single heater configuration is recommended for better performance at low load, however, additional iterations between the 1D and CFD models are suggested for further work.